Growth and yield promoting effect of NPK fortified with pressmud compost on sugarcane - Asghar, Muhammad Shahbaz; Afzal, Muhammad (Journal of Scientific Agriculture, 2020)
Combined application of press mud compost and inorganic fertilizers is a cost effective way to manage soil fertility in a sustainable way. To evaluate the results of press mud compost and inorganic based synthetic fertilizers, the present study was planned and research was conducted at Sheikhoo Sugarcane Research Farm located at Sheikhoo Sugar Mills, Kot Addu. The experiment was consist of six treatments namely T1 = No fertilizer, T2 = NPK 228-114-124 kg ha-1, T3 = 25 t ha-1 compost, T4 = NPK 228-114-124 kg ha-1+ 20 t ha-1 compost, T5 = NPK 114-57-62 kg ha-1+ 20 t ha-1 compost and T6 = NPK 228-114-124 kg ha-1+ 10 t ha-1 compost and was laid out in RCB design having four replications with a net plot size of 6 m x 8 m. Sugarcane growth and yield parameters including soil fertility levels (pre planting and post harvesting) were studied. Results showed that lower pH value (8.42) and higher organic matter contents (0.42) were recorded in treatment having compost @ 25 t ha-1. Whereas, higher N (0.028 %), P (7.27 ppm) and K (68.25 ppm) were found in those soils which were treated with NPK 228-114-124 kg ha-1+ 20 t ha-1 compost. Results regarding sugarcane growth and yield showed that maximum number of tillers (138.50 x103 ha-1) 135 days after planting, number of millable cane (104.25 x103 ha-1), number of nodes (25.25/ cane), cane girth (7.54 cm), cane length (3.89 m), cane yield (111.75 t ha-1), brix (22.08 %), pol (19.80 %) and sugar recovery (10.75 %) were observed in those plots treated with NPK 228-114-124 kg ha-1+ 20 t ha-1 compost. It can be concluded that the combined use of press mud compost and inorganic NPK fertilizers remained successful to promote the growth as well as the yield of sugarcane and soil fertility improvement in an efficient way.